(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The paper is focused on Jelena Dimitrijević’s novel Nove (1912) and the women’s issue, that is, the place of women in the oriental society at the turn of the 20th century. Through the main character, girl Fatma, educated on European role models that were based on the traditions of Enlightenment and sentimentalism, the author has made an insight into the position of woman in the closed societies. She also depicts the beginning of the rebellion of young and learned women against the strictly organised patriarchal society of the oriental type. Their self-consciousness is accompanied by personal sacrifices. Jelena Dimitrijević also presented a general overview of the period before the Young-Turk revolution (1908).